PERAN INOVASI, PEMASARAN DIGITAL, MODAL DALAM MENINGKATKAN PENJUALAN UMKM BERBASIS SYARIAH DI JAKARTA - Ghibran Al Farizi; Hartutik Hartutik (Taksasila Edukasi Insani, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy as drivers of economic growth, labor absorbers, and instruments for poverty reduction. The significant contribution of MSMEs to Gross Domestic Product (GDP) and employment makes this sector the backbone of the national economy, including in maintaining economic stability during times of crisis. In the context of Islamic MSMEs, improved business performance is strongly influenced by the ability to innovate, mastery of digital marketing, and access to business capital in accordance with Sharia principles. Innovation based on Islamic values, whether in products, processes, or business models, can increase competitiveness and attract Muslim consumers. Furthermore, digital marketing is a crucial tool for expanding market reach and building customer loyalty, although digital skills remain limited among Islamic MSMEs. On the other hand, limited access to Islamic financing and low financial literacy are key challenges to business development. Therefore, increasing innovation, strengthening digital capacity, and optimizing Islamic financing are key factors in driving the growth and sustainability of Islamic MSMEs.Keywords: The Role of Innovation, Digital Marketing, Capital and Increasing MSME Sales